Computational study of electronic influence of guanidine substitution on diels-alder reactions of heterocyclic dienes - Antol, Ivana (Array, 2019)
Quantum-chemical calculations of cycloaddition properties of cyclic heterodienes substituted with guanidine functionality were carried out. Molecular and electronic structures of series of dienes (pyrrole, furan, thiophene, isoindole and 1,3-butadiene) were calculated and reactivity order established on the basis of FMO theory. Transition state calculations of model [4+2] cycloaddition reaction with acetylene indicate that guanidine substitution influences reaction barriers in moderate extent (up to ~4 kcal mol–1). The substitution position plays an important role on the sign and magnitude of the effect and protonation of nitrogen possessing substituents increases reactivity of dienes.